Subcellular organisation of the cAMP signalling pathway - Zaccolo, M; Zerio, A; Lobo, MJ (American Society for Pharmacology and Experimental Therapeutics, 2020)
The field of cAMP signaling is witnessing exciting developments with the recognition that cAMP is compartmentalized and that spatial regulation of cAMP is critical for faithful signal coding. This realization has changed our understanding of cAMP signaling from a model in which cAMP connects a receptor at the plasma membrane to an intracellular effector in a linear pathway to a model in which cAMP signals propagate within a complex network of alternative branches and the specific functional outcome strictly depends on local regulation of cAMP levels and on selective activation of a limited number of branches within the network. In this review, we cover some of the early studies and summarize more recent evidence supporting the model of compartmentalized cAMP signaling, and we discuss how this knowledge is starting to provide original mechanistic insight into cell physiology and a novel framework for the identification of disease mechanisms that potentially opens new avenues for therapeutic interventions.